(untitled) (CIPEEX, 2025)
The advent and rapid expansion of the internet have transformed electoral advertising into the primary channel of communication for political candidates. However, the proliferation of fake news and manipulative practices within this environment has prompted the legislature to introduce targeted regulatory measures for the digital sphere. This qualitative, descriptive, and analytical study examines the regulation of digital electoral advertising under Brazilian law, identifying the normative frameworks established and the challenges posed by ongoing technological evolution. The study, conducted through qualitative, descriptive, and analytical methods, relies on a documentary and normative examination of legislation, including Brazilian Law nº 9.504/1997, Law nº 12.034/2009, the Electoral Code, and resolutions of the Brazilian Superior Electoral Court (TSE), complemented by legal scholarship and academic articles to delineate the rules and limitations governing digital electoral advertising in Brazil. The results indicate that the regulatory framework originated in TSE resolutions and was consolidated through Law nº 12.034/2009, which established requirements for the use of websites, social networks, and blogs, mandating prior registration with the Electoral Justice and clear identification of sponsors, while prohibiting anonymous advertising, automated bot activity, negative paid promotion, and the misuse of personal data. Technological advances pose challenges such as the rapid dissemination of fake news, which threatens democratic stability, and the difficulty of balancing freedom of expression with the containment of abuses in a decentralized digital environment, underscoring the necessity for continuous legal adaptation and more effective mechanisms to ensure a fair and transparent electoral process. In conclusion, Brazilian electoral law recognizes the central role of the internet in political campaigns, instituting regulations to safeguard freedom of expression while curbing abuses such as fake news, anonymity, and the creation of false profiles, with the ongoing challenge of striking a balance between such freedoms and the protection of the electoral process, a task that demands continual legislative revision and proactive oversight by the Electoral Justice, public authorities, and civil society to guarantee democratic and transparent elections.